On minimal ω-composition non-H-formations - Belous, L.I.; Selkin, V.M. (Algebra and Discrete Mathematics, 2006)
Let H be some class of groups. A formation F
is called a minimal τ -closed ω-composition non-H-formation [1] if
F * H but F1 ⊆ H for all proper τ -closed ω-composition subformations F₁ of F. In this paper we describe the minimal τ -closed
ω-composition non-H-formations, where H is a 2-multiply local formation and τ is a subgroup functor such that for any group G all
subgroups from τ (G) are subnormal in G.